(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Digitalization and inter-connectedness of business systems have increased the dependency between business entities. The ever-changing environment and business demands have increased competition and collaboration among diverse entities, which have forced the concept of ecosystem models. This work highlights the need for a digital tourism business ecosystem model for the tourism industry of Nepal. The work is built on interviews with experts from the Nepal tourism sector and the study of literature, reports, and publications in the field of tourism and digitalization in tourism of Nepal. Interviews are carried out on a one-to-one basis with 30 selected industry experts as a source of information and data. The study builds a taxonomy of different scenarios of tourism, a conceptual model for the Digital Tourism Business Ecosystem, and an Implementation model for Nepal. Further, as the selection of resources is a crucial factor in Digital Business Ecosystem, an Analytical hierarchical processing model is proposed as a solution for resource selection and optimization. This work is important as it brings out the need for a Digital Tourism Business Ecosystem in today’s context, especially for the tourism industry. Secondly, it demonstrates the practical aspects of the Digital Tourism Business Ecosystem Model for Nepal. The work can further serve as a reference and knowledge base for digital business system analysts, system designers, and digital tourism business implementers for better digital business system designs and implementation in the tourism sector.